KAJIAN ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI DALAM PENDIDIKAN ISLAM DI INDONESIA - Tilsep Jasnain Jasnain (Jurnal Al-Fatih, 2022)
ABSTRACT: This paper aims to describe and describe aspects of ontology, epistemology and axiology in Islamic education in Indonesia. In the ontology aspect, Islamic education is generally oriented to form human beings and to integrate the theory of Fitrah. In the epistemological aspect of Islamic education in Indonesia, it examines the development of theory. Discussing things related to knowledge, whether it's "how to get", "how to flow / ins and outs", or "how to method" in getting a science in education. In the axiological aspect of Islamic education in Indonesia, it examines the values concerning the benefits and uses of studying Islamic education it self.